Diffusion and the employment effects of information and communication technology. - Freeman, Chris; Soete, Luc; Efendioglu, Umit (International Labour Review, 1995)
Part of a special issue on employment policy in the global economy. Information and communication technology (ICT) has had tremendous global influence, arguably ushering in a new, postindustrial age. ICT both creates and destroys jobs, and it lowers costs, counters inflation, and increases competitiveness. However, the shift toward a knowledge-based economy has particularly adverse effects on the employment and wages of unskilled manual workers, and there is a need for a major shift in education and skills provision for new forms of employment for excluded, unskilled workers. The role of ICT in the success of the dynamic Asian economies is examined.